Special solutions of coupled classical harmonic oscillators with the addition of magnetic monopoles - Rundberget, Charlotte (Physics open, 2025)
In this paper, we undertake a thorough investigation into the existence of magnetic monopoles, elusive particles theorized to possess isolated north or south magnetic poles. These hypothetical entities have long captured the imagination of physicists and have been the subject of extensive research. Our analysis, rooted in the principles of classical mechanics and electrodynamics provides a unique look into the fundamental nature of these hypothetical monopoles.